The Effect of Experience Quality on Customer Loyalty (Evidence From a Coffee Shop) - Kartika, Nurullaily; Usman, Indrianawati; Lestari, Yetty Dwi; Wurjaningrum, Febriana; ​Auliandri, Tuwanku Aria​; Barinta, Dunga Dwi; Chrysanti, Laurencia (JURNAL AKUNTANSI DAN MANAJEMEN, 2025)
The study aims to examine the influence of experience quality on customer perceived value and customer satisfaction, and to see its impact on Amstirdam Coffee customer loyalty. Respondents in this study numbered 222 people who are Amstirdam Coffee customers and have visited and purchased Amstirdam Coffee products more than once. Data collection in this study was conducted by distributing online questionnaires. This study used Structural Equation Modeling (SEM) and was tested using SmartPLS software.  The results show a positive and significant influence of experience quality on customer perceived value and customer satisfaction. However, this study also found a positive, insignificant relationship between experience quality and customer loyalty.